The Effect of Online Family-Centered Care on the Lifestyle of Adolescent Girls with Obesity - FatemehSadat SeyedNematollah Roshan; Marjan Akhavan Amjadi; Sahar MahjoubVaghaeh Dashti (Patient Safety and Quality Improvement Journal)
Introduction: Obesity is associated with many adverse health consequences. Apart from the problem of genetics, an unfavorable lifestyle can be the main cause. Due to significant technological advances and widespread acceptance by adolescents, technology can now be used to improve their lifestyles. This study assessed the effectiveness of online family-centered care on the lifestyle of adolescent girls with obesity. Materials and Methods: This semi-experimental study was conducted after choosing 60 adolescent girls with obesity divided into two groups randomly. The research tools included demographic and HPLP_II questionnaires. 11 online sessions were held for the case group. The post-test was carried out after 1.5 months. Results: After the intervention, there was a significant difference between the control (112.23±8.53) and case (125.8±10.91) in the mean score of the Lifestyle (P<0.001). In contrast, before the intervention independent t-test showed no significant difference between the two groups (P=0.397). Before the study, the mean weight and BMI were not statistically significant between the two groups (P=0.511 and P=0.063). After the intervention, there were significant changes in girls’ weight (P=0.023) and BMI (P=0.144). Conclusion: Results showed that family-centered care through new communication technologies effectively improved the lifestyle of adolescent girls with obesity.